Screening study of nerve growth factor's and brain-derived neurotrophic factor's mimetics effects at the experimental depression model - A. G. Mezhlumyan; A. V. Tallerova; P. Yu. Povarnina; N. M. Sazonova; A. V. Tarasiuk; T. A. Gudasheva (Фармакокинетика и Фармакодинамика)
At the Zakusov Institute of Pharmacology designed and synthesized dimeric dipeptide mimetics of the 1st (GK-6) and 4th (GK-2) nerve growth factor loops, 1st (GSB-214), 2nd (GTS-201) and 4th (GSB -106, GSB-106Ac) brain-derived neurotrophic factor loops. Antidepressant activity of GSB-106 has already been established by oral and intraperitoneal administration in 0.1-5.0 mg/kg doses. Newly synthesized mimetics were studied in comparison with GSB-106 for antidepressant-like activity in the forced swim test on male Balb/c mice with a single intraperitoneal administration. It was found that only mimetic of the fourth brain-derived neurotrophic factor loop GSB-106Ac, varied from GSB-106 by replace monosuccinyl fragment to acetyl, has antidepressant activity in doses of 1.0 mg / kg and 5.0 mg / kg.